Electropolymerization of D–A–D type monomers consisting of triphenylamine and substituted quinoxaline moieties for electrochromic devices. (5th October 2021) - Fu, Wenan; Chen, Hongjin; Han, Yiying; Wang, Wenyuan; Zhang, Rui; Liu, Jian
Abstract : We reported three D–A–D type monomers consisting of triphenylamine and substituted quinoxaline moieties, and their electrochemical polymerization for electrochromic devices. Abstract : Three novel donor–accepter–donor (D–A–D) type monomers (TPAQ-Ph, TPAQ-PhOMe and TPAQ-Phen ) consisting of triphenylamine (TPA) and substituted quinoxaline moieties were synthesized, and further electropolymerized for electrochromic devices. Polymers PTPAQ-Ph and PTPAQ-PhOMe with two twisted substituents on the π-conjugated backbone exhibited efficient electrochromic properties, involving high optical contrast up to 70%, short response time less than 3 s, high color coloration efficiency over 200 cm 2 C −1, and good cycle stability. However, polymer PTPAQ-Phen employing a fused electron acceptor unit with high coplanarity showed poor electrochromic performance and low stability. Moreover, electrochromic devices based on these three polymers were fabricated and characterized. The result demonstrates that the molecular configuration of the designed monomer is crucial for electrochromic performance.